FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI POLITIK PEMILIH PADA PEMILIHAN PRESIDEN (PILPRES) TAHUN 2019 DI KOTA PEKANBARU - Jannah, Khai Rati; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
General elections are the main means for people to demonstrate their political rights in electing representatives of the people who will take control of the wheels of the nation's and future journey. The 2019 Presidential Election in Pekanbaru City experienced an increase in voter turnout, reaching 78.90% when compared to previous elections and even exceeding the KPU's target of 77%. High voter participation is a marker of concern for democratic citizens, while low voter participation is an indicator of apathy and distrust of citizens towards the political process. This study aims to look at the factors that influence the political participation of voters. The theory used in this research is Milbrath's theory regarding the factors that influence participation. This research uses descriptive method with qualitative research type. The type of data used in this research is primary data, namely interviews and secondary data obtained from literature study, documentation and observation. The results of this study found that the increasing political participation of Pekanbaru City voters in the 2019 Presidential Election was influenced by five factors, namely, political stimulation factors carried out by the Pekanbaru City KPU and election organizers, political parties as well as candidates and candidates and their success teams, personal characteristics factors. Pekanbaru City voters who are already rational, the social characteristics of voters, where education in Pekanbaru City is high and is a city center that tends to have a broad educated and insightful community, the situation and political environment during the 2019 Presidential Election, the situation is very interesting because of the rematch of two people who had running in the 2014 election, and the political education factor carried out by the election management institution and the political community. But of the five factors the most dominant influence is the political incentive factor and the factor of the political environment.  Keywords: Political Stimulation, Voters Personal Characteristics, Voters' Social Characteristics, Political Situation, Political Education.